PENGEMBANGAN BUKU PANDUAN MENULIS CERPEN SISWA KELAS IX SMP N 4 KAJEN KABUPATEN PEKALONGAN - Sismulyanti SB, Nugraheti (Lembaran Ilmu Kependidikan, 2010)
This study departed from the fact that often teachers find difficulties in selectingappropriate materials. It is assumed that the students' low grade in basic competenceto write short story is attributed to their poor ability and motivation to write as well asthe teachers' poor selection of learning materials. In response to this situation, thepresent study developed a book specifically designed to improve the students' abilityto write a short story. To bring this aim into practice this project took 30 junior highschool students and 6 teachers of three junior high schools of Pekalongan District,Central Java. All were purposively selected. Following research and developmentmodel of research suggested by Borg and Gall (cited in Sukmadinata 2008:169), thisstudy found that: (1) in terms of the profile of the book, the students were interestednot only in its interesting cover but also in its handy form. Besides, it used easilyunderstood language and the price was reasonable; (2) the experts' examinationshowed that the prototype of the book could feasibly be used for supporting theteachers' instructional practice; and (3) the book was effective to support teachers'instructions. This study is preliminary in nature however, and therefore a furthercomprehensive study is needed in the future to fill in the gap this study may still leave.Kata Kunci : menulis cerpen, buku panduan, siswaSMP